1996
DOI: 10.1039/cc9960002225
|View full text |Cite
|
Sign up to set email alerts
|

Novel and efficient synthesis of sulfur-containing heterocycles using a hypervalent iodine(III) reagent

Abstract: A novel and efficient synthesis of sulfur-containing heterocycles from phenol ethers bearing an alkyl sulfide sidechain using a combined reagent of a hypervalent iodine(u1) species and BF3.Et20 is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The spots and bands were detected by UV irradiation (254, 365 nm). was synthesized by the method in the literature, 31) i.e., BF 3 ·Et 2 O (268 mL, 2.12 mmol) was added to a solution of 2-deoxy-2-phthalimido-1,3,4,6-tetra-O-acetyl-D-glucopyranose (676 mg, 1.41 mmol), and p-octyloxybenzenethiol (506 mg, 2.12 mmol) in dichloromethane (5 mL) at 0°C and the mixture was stirred for 20 h at room temperature (r.t.). After the reaction, the reaction mixture was poured into ice water and extracted with ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spots and bands were detected by UV irradiation (254, 365 nm). was synthesized by the method in the literature, 31) i.e., BF 3 ·Et 2 O (268 mL, 2.12 mmol) was added to a solution of 2-deoxy-2-phthalimido-1,3,4,6-tetra-O-acetyl-D-glucopyranose (676 mg, 1.41 mmol), and p-octyloxybenzenethiol (506 mg, 2.12 mmol) in dichloromethane (5 mL) at 0°C and the mixture was stirred for 20 h at room temperature (r.t.). After the reaction, the reaction mixture was poured into ice water and extracted with ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30] We have been engaged in the development of the oxidation of the sulfur atom utilizing hypervalent iodine reagents to form an active iodonium intermediate. 31,32) Thus, we have recently developed novel methods of hypervalent iodine-induced glycosylation of thioglycoside. 33) Besides our study, a few methods have been reported as for the activation of thioglycosides with hypervalent iodines to date [34][35][36] ; however, activation of disarmed thioglycosides with hypervalent iodines still remains impractical and unavailable in the synthesis of biologically active oligosaccharides.…”
mentioning
confidence: 99%
“…As for the chemical oxidation of 1 a with heavy metals, glaucine ( 3 a ) was usually obtained in moderate to good yields 10. Similar to heavy metal oxidation, the reaction of 1 a with PIFA/BF 3 ⋅Et 2 O in CH 2 Cl 2 gave 3 a in 58 % yield (entry 1) 12e. On the contrary, application of our prior conditions,13b the combination of PIFA and tungsto( IV ) phosphoric acid (H 3 [PW 12 O 40 ], ca.…”
Section: Resultsmentioning
confidence: 95%
“…As a result, we have developed the direct oxidative nucleophilic substitution of phenyl ethers with various nucleophiles using phenyliodine(III) bis(trifluoroacetate) (PIFA). [55][56][57] In further study, a combination of Lewis acid and PIFA was used to identify a biaryl coupling reaction of phenyl ether and alkyl arene via a cation radical intermediate. [58][59][60][61][62][63] The coupling reaction proceeds via cation radicals with the neutral molecule of the substrate to obtain a coupling product.…”
Section: Introductionmentioning
confidence: 99%